Reciprocal Contributions between People and Nature: A Conceptual Intervention - Ojeda Villarroel, Jaime Andrés; Salomon, Anne K.; Rowe, James K.; Ban, Natalie C. (My University, 2022)
Throughout human history, Indigenous and local communities have stewarded nature. In the present article, we revisit the ancestral principle of reciprocity between people and nature and consider it as a conceptual intervention to the current notion of ecosystem services commonly used to inform sustainability transformation. We propose the concept of reciprocal contributions to encompass actions, interactions, and experiences between people and other components of nature that result in positive contributions and feedback loops that accrue to both, directly or indirectly, across different dimensions and levels. We identify reciprocal contributions and showcase examples that denote the importance of reciprocity for our ecological legacy and its relevance for biocultural continuity. We suggest that the concept of reciprocal contribution can support transformation pathways by resituating people as active components of nature and restructuring institutions so that ethical principles and practices from Indigenous and local communities can redirect policy approaches and interventions worldwide.
Keywords: reciprocity; empathy; stewardship; sustainability; biodiversity conservation